A Correlation Between Knowledge and The Role of Health Workers with Family Ownership of Health Toilets among The Community in Coastal Area of Sinar Jaya Village, Kaur Tengah Sub-District - Emi Kasih Lestari; Darmawansyah Darmawansyah; Wulandari Wulandari (Student Scientific Journal, 2026)
Background: Sanitation development issues are socio-cultural problems, one of which is the behavior of residents who are accustomed to defecating in public places. According to data from the Indonesian Ministry of Health, 25% of the population uses unsanitary toilets and 17.7% still defecate in public places. Data from the Tanjung Iman Health Center in 2024 shows that only 57.3% of families have toilets, which is far from the government's target of 80%. Data from Sinar Jaya Village shows that 73.33% of respondents living in the watershed area practice open defecation in rivers. In addition, 66.6% of the community did not know the benefits of toilets, the requirements for healthy toilets, or the impact of open defecation in rivers, so the community did not want to have family toilets. Objective: The purpose of this study is to determine a correlation between knowledge and the role of health workers with the family ownership of healthy toilets among the coastal community of Sinar Jaya Village. Method: This study is a quantitative study using a cross-sectional design. The population consisted of 352 respondents. The sampling technique used was simple random sampling. The number of samples found was 80. The analysis used was univariate analysis and bivariate analysis with the Chi-Square test. Research results: Almost all of the respondents did not have a family toilet, a small number of respondents had insufficient knowledge, and a small number of respondents had health workers who did not support them. There was a correlation between knowledge (p=0.000) and the role of health workers (p=0.003) and the ownership of family toilets. Conclusion : The suggestion for future researchers is to investigate the socio-cultural behavioral factors related to family toilet ownership using multivariate analysis and in-depth interviews.